Kendala Mahasiswa Calon Guru IPA Menyusun Eksplanasi Ilmiah pada Konten Listrik dan Aplikasi pada Mahluk Hidup - Agustina, Tri Wahyu; Handayani, Wahyuni; Millah, Roprop Latiefatul (Universitas Sebelas Maret, 2022)
The main objective of science education is to prepare students to synthesize and evaluate scientific explanations. Students still have difficulty using the principles of science in proving scientific claims. This study aims to identify the obstacles faced by prospective science teacher students in preparing scientific explanations for the content of Static Electricity and Applications to Living Things. Descriptive research. Purposive sampling in semester 2 A amounted to 16 students. Learning uses the premise-reasoning-outcome-visual representation strategy to develop scientific explanations. Instruments using a questionnaire include four structured questions about the facts or principles of electricity, explanations of the causes of electrical phenomena in living things, explanations of electrical phenomena, and visual representation of electricity. Data analysis uses percentages based on specific criteria. Most of the students, as much as 57%, can express facts or principles of electricity. Most students, namely 50%, cannot explain electrical phenomena in living things. As many as 57% of students can explain electrical phenomena in everyday life. Almost all students, i.e., 79%, did not experience problems visually representing electrical phenomena. The study results showed that there were still students who had problems preparing scientific explanations. The main obstacle is that students have not been able to relate the explanation of electrical phenomena to living things. The implications of the research are to equip students to integrate science content, namely Physics and Biology.